Prevalence of delirium in elderly intensive care unit patients of a tertiary care medical college hospital - S. R., Hemanth Kumar; Patel, Apoorva E. (International Journal of Advances in Medicine, 2019)
Background: Delirium is an acute disorder of attention and cognition. It occurs in 20% to 79% of hospitalized older patients. It is also common in ICU patients, occurring in 20% to 50% of non-mechanically ventilated ICU patients and in 60% to 80% of mechanically ventilated ICU patients. Hence delirium is a common, serious, and often fatal condition among older patients. The present study attempts to address the prevalence of Delirium in the Indian elderly population. Methods: A cross sectional study was conducted between January 2019 to June 2019 in a 50 bedded intensive care unit of a tertiary care hospital in Bengaluru, Karnataka. A total of 300 elderly patients aged 60 years and above, satisfying the inclusion criteria was included in the study. Patients were assessed for the presence of delirium within 24 hours of admission using Confusion Assessment Method for Intensive Care Unit (CAM-ICU). Various qualitative variables were expressed in terms of proportions. Results: Prevalence of delirium among elderly, non-ventilated ICU patients was 30% (90 out of 300 patients). Among them, 50 (55.5%) were females and remaining 40 (44.5%) were males. Mean age of the patients was 76 years. About 50 (55.5%) of them belonged to age group of 70-79 years. Most of the delirium patients (44.5%) belonged to hypoactive type of delirium followed by hyperactive (33.3%) and mixed (22.2%) type of delirium. Conclusions: Delirium in elderly ICU patients is significantly prevalent, which is a poor prognostic factor, leading to higher morbidity and mortality. Of the three subtypes- hypoactive delirium is the most common type of delirium among elderly. Yet, it is often overlooked or under-diagnosed. Hence clinicians and/or trained nursing staff managing the patients in the ICUs, should routinely screen the patients for delirium, using brief screening measures, which in turn can improve the patients’ outcome.